Exploring the impact of HIV infection and antiretroviral therapy on placenta morphology. (15th January 2021) - Yampolsky, Michael; Shlakhter, Oleksandr; Deng, Dianna; Kala, Smriti; Walmsley, Sharon L.; Murphy, Kellie E.; Yudin, Mark H.; MacGillivray, Jay; Loutfy, Mona; Dunk, Caroline; Serghides, Lena
Abstract: Introduction: Women living with HIV experience more adverse birth outcomes; the mechanisms are not fully understood. We examined placenta morphology and associations with birth outcomes in a Canadian cohort of women living with HIV (HIV + ) on antiretroviral therapy (ART) from conception and HIV-uninfected (HIV − ) women. Methods: Term placentas from 94 women (40 HIV −, 54 HIV + ) were studied. Trimmed placenta weight was collected. Placenta digital photos were used to compute morphometric parameters. Regression models investigated associations between log-transformed placenta parameters and birth outcomes. Results: We observed a trend towards lower placenta weight and smaller placenta area in the HIV + group, both of which were significantly associated with small for gestational age births. HIV + serostatus was associated with 6-fold (95%CI 2–20) greater odds of having placenta area in the lowest quartile (<236 cm 2 ). Cord marginality (distance from the edge) was significantly lower in the HIV + group (p = 0.004), with 35% of placenta having an abnormal (marginal or velamentous) cord insertion vs. 12.5% in the HIV − group (p = 0.01). Velamentous cord insertion was seen in 13% of placentas in the HIV + vs. 0% in HIV − group (p = 0.02). A significant correlation between cord marginality and placenta thickness was observed in the HIV − group, with a more marginal cord being associated with a thicker placenta. This correlation was not observed in the HIV + group. HIV + placentas exposed to protease inhibitors were significantly less circular compared to the HIV − group (p = 0.03). Conclusion: Our data suggest that HIV/ART exposure affects placenta morphology and is associated with higher rates of abnormal cord insertion. Highlights: HIV-positive serostatus is associated with higher rates of abnormal umbilical cord insertion. HIV-positive serostatus is associated with placentas with smaller area and lower weight. Protease inhibitor exposure is associated with non-circular placentas.